Interlanguage Errors Made By Eleventh Grade Students Of SMA 1Dagangan In Writing Recount Text 2013/2014 - Budiyanto, Budiyanto, Agus Wijayanto, Ph.D, Dra. Siti Zuhriah Ariatmi, M.Hum (2014)
The thesis describes the interlanguage errors made by the students in writing recount text at SMAN 1 Dagangan. By doing the research, the researcher could investigate the errors and the classification of errors, the possible factor that contribute to the errors made by students at SMAN 1 Dagangan based on the surface strategy taxonomy. Subjects of the research are the students at elevent grade at SMAN 1 Dagangan. The data collection was conducted through students' test in writing recount text. The data collection was analyzed by using qualitative research. The result of the research showed that the total 499 errors were identified. Of them 207 (41,5%) were errors of ommision, 97 (19,5%) were errors of addition, 119 (23,8%) were errors of misformation and 76 (15,2%) were errors of misordering. Based on the finding above the characteristics of the errors : systematicity (46,9%), permeability (30,7%), dynamicity (22,4%). There are three factors that contibute to the errors that made by the students, the first is the language transfer or interlingual transfer, second is overgeneralization and the last factor is influence of mother tongue. .